THE RIGHTS OF NONMUSLIM IN DRESSING (THE COMPARATIVE STUDY OF QANUN NO. 11 OF 2002 AND HUMAN RIGHTS) - Danil Putra Arisandy (Proceeding International Seminar of Islamic Studies, 2022)
This paper seeks to describe Qanun Acehs provisions on Islamic dress in particular autonomous regions. The enactment of Muslim clothing in Aceh as a provision that is compared to other regions in Indonesia is an exciting theme reviewed in this article, significantly when it is associated with the existence of nonmuslim groups as a minority using the library research method this paper seeks to compare between the concept of dressing in Qanun No. 11 of 2002 and Human Rights. The methodological creation concluded that the implementation of Qanun dressed in Islamic dress does not violate human rights for a group of minorities in the area of Islamic sharia. Especially after the release of Law No. 18 of 2001 concerning Autonomy for Aceh, one of the distinctive areas can make special rules to create public order. In other words, the enactment of Qanun dressed in Islamic dress in the context of regional autonomy has been capable of procedure and is constitutional and not counterproductive to the conception of human rights.Keywords:dressing, nonmuslim, Aceh, human rights, comparative study